R-phycoerythrin alginate/shellac beads by external gelation: Process optimization and the effects of gastrointestinal digestion for nutraceutical applications. - Castro Varela, Pablo Andrés; Rubilar, Mónica; Martínez-Férez, Antonio; Fuentes-Ríos, David; López-Romero, Juan Manuel; Alarcón, Claudio; Abdala-Díaz, Roberto Teófilo; López-Figueroa, Félix (Elsevier, 2024)
This study aimed to evaluate an alginate/shellac mixture as wall material to develop an aqueous phycoerythrin (R-PE) encapsulation system by external gelation and to determine the effect of encapsulation on the biological properties of R-PE released during simulated gastrointestinal digestion. The Taguchi method was implemented to formulate beads with a high R-PE encapsulation efficiency (EE). The effect of the variables: feeding flow (90 and 20 mL h− 1), distance (5 and 10 cms), and CaCl2 (5 and 15 g L− 1) were optimized, and the bead size, sphericity factor (SF), and total R-PE content were characterized. Finally, the optimal alginate/shellac beads were subjected to in vitro dynamic gastrointestinal digestion. The results show that the beads formed under optimal conditions reached an EE value of 97.5 %. The CaCl2 concentration and feeding flow most affected the R-PE EE. The release of R-PE from alginate/shellac was affected at acid pH 1; however, the concentration was under 10 % of the total R-PE content showing promising targeting properties in terms of time and pH. The R-PE extracts and capsules were partially degraded in gastric and intestinal conditions; the mouth did not detect signals from the protein profile. The encapsulation of alginate/shellac led to higher R-PE contents at the end of digestion than non-encapsulated R-PE, suggesting a protective role. Significantly, from permeate streams, equivalent to the absorption of encapsulated R-PE, the bioavailability was 2.5 times higher than non-encapsulated R-PE. NMR results indicate the presence of R-PE and its methyl amino acids and oligosaccharides between 0.5 and 2.5 and 3.8–6.8 ppm, respectively. Cytotoxicity activity was observed for the R-PE extract on the HCT-116 human colon cancer cell line. The alginate/shellac as a wall material and ionic gelation technology used may determine the release of the R-PE pigment at an intestinal site and its antiproliferative effect on health.
Keywords: Nanotecnología; Polímeros; Industria farmacéutica; Materiales compuestos; Alginate/shellac; Ionic gelation; Simulated gastrointestinal digestion; Antiproliferative activity